Effects of cytokines derived from cancer-associated fibroblasts on androgen synthetic enzymes in estrogen receptor-negative breast carcinoma - Kikuchi, Kyoko; McNamara, Keely May; Miki, Yasuhiro; Moon, Ju-Yeon; Choi, Man Ho; Omata, Fumiya; Sakurai, Minako; Onodera, Yoshiaki; Rai, Yoshiaki; Ohi, Yasuyo; Sagara, Yasuaki; Miyashita, Minoru; et al. (SPRINGER, 2017)
The tumor microenvironment plays pivotal roles in promotion of many malignancies. Cancer-associated fibroblasts (CAFs) have been well-known to promote proliferation, angiogenesis, and metastasis but mechanistic understanding of tumor-stroma interactions is not yet complete. Recently, estrogen synthetic enzymes were reported to be upregulated by co-culture with stromal cells in ER positive breast carcinoma (BC) but effects of co-culture on androgen metabolism have not been extensively examined. Therefore, we evaluated roles of CAFs on androgen metabolism in ER-negative AR-positive BC through co-culture with CAFs. Concentrations of steroid hormone in supernatant of co-culture of MDA-MB-453 and primary CAFs were measured using GC-MS. Cytokines derived from CAFs were determined using Cytokine Array. Expressions of androgen synthetic enzymes were confirmed using RT-PCR and Western blotting. Correlations between CAFs and androgen synthetic enzymes were analyzed using triple-negative BC (TNBC) patient tissues by immunohistochemistry. CAFs were demonstrated to increase expressions and activities of 17 beta HSD2, 17 beta HSD5, and 5 alpha-Reductase1. IL-6 and HGF that were selected as potential paracrine mediators using cytokine array induced 17 beta HSD2, 17 beta HSD5, and 5 alpha-Reductase1 expression. Underlying mechanisms of IL-6 paracrine regulation of 17 beta HSD2 and 17 beta HSD5 could be partially dependent on phosphorylated STAT3, while phosphorylated ERK could be involved in HGF-mediated 5 alpha-Reductase1 induction. alpha-SMA status was also demonstrated to be significantly correlated with 17 beta HSD2 and 17 beta HSD5 status in TNBC tissues, especially AR-positive cases. Results of our present study suggest that both IL-6 and HGF derived from CAFs could contribute to the intratumoral androgen metabolism in ER-negative BC patients.
Keywords: STROMAL FIBROBLASTS; CELL-PROLIFERATION; GENE-EXPRESSION; ACTIVATION; GROWTH; STAT3; INTERLEUKIN-6; AROMATASE; SUBTYPES; MICROENVIRONMENT